2014
DOI: 10.1021/ac503176d
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Glassy Carbon Surface Oxides in Non-Aqueous Voltammetry: The Case of Quinones in Acetonitrile

Abstract: Glassy carbon (GC) electrodes are well-known to contain oxygenated functional groups such as phenols, carbonyls, and carboxylic acids on their surface. The effects of these groups on voltammetry in aqueous solution are well-studied, but there has been little discussion of their possible effects in nonaqueous solution. In this study, we show that the acidic functional groups, particularly phenols, are likely causes of anomalous features often seen in the voltammetry of quinones in nonaqueous solution. These fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 48 publications
3
27
0
Order By: Relevance
“…The results suggest that during the preanodisation a highly resistive layer forms which is the product of acetonitrile electrooxidation. The surface of glassy carbon is usually covered by phenolic and oxo functional groups and they can bond substrate and product molecules through hydrogen bounds in acetonitrile leading to diminished currents after the first scan which was verified in the investigation of quinones [18]. At higher potentials acetonitrile can be oxidized also on its methyl group and the formed radicals can couple with the surface phenolic hydroxyl groups making less accessible the electrode surface for the substrate molecules.…”
Section: Preanodisation Of Glassy Carbon Electrode In Acetonitrile Atmentioning
confidence: 91%
“…The results suggest that during the preanodisation a highly resistive layer forms which is the product of acetonitrile electrooxidation. The surface of glassy carbon is usually covered by phenolic and oxo functional groups and they can bond substrate and product molecules through hydrogen bounds in acetonitrile leading to diminished currents after the first scan which was verified in the investigation of quinones [18]. At higher potentials acetonitrile can be oxidized also on its methyl group and the formed radicals can couple with the surface phenolic hydroxyl groups making less accessible the electrode surface for the substrate molecules.…”
Section: Preanodisation Of Glassy Carbon Electrode In Acetonitrile Atmentioning
confidence: 91%
“…Several electrochemical studies have been carried out regarding the reduction of quinones, mainly to gain insights about the underlying mechanisms and the effects provoked by changing conditions such as electrolytic medium and electrode surface, among others [ 22 ]. A study on the effects of hydrogen bonds in different Q/HQ systems in non-aqueous media showed that the presence of oxygenated functional groups on the surface of the electrode could affect the interaction between dissolved compounds and the surface, which had a significant impact on the electron transfer process [ 23 ]. The electrochemistry of quinones in the presence of added hydroquinone as a hydrogen bonding proton donor, the effective pH at the electrode surface [ 24 ] as well as the electrochemical effect of CO 2 in dimethylformamide solution, were all studied [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Am echanism involving as ingle binding step (K 1Q )w ith subsequent ET (E 2 )w as found to best describe the experimental data. [29] As noted above,t hese simulations revealed that bis(amidinium) salt 4 binds QC À as a1 :1 complex, in contrast with HBDs 1-3,w hich form 2:1c omplexes with QC À .B ecause of this change in stoichiometry,t he efficacyo ft he different HBDs in promoting ET to Q was gauged by comparing the value of K Q C À for 4 to that of K 1Q C À K 2Q C À for 1-3.T his analysis reveals that 4 is exceptionally effective at promoting ET and six orders of magnitude more potent than 2 at binding QC À .…”
mentioning
confidence: 99%